The Global Challenges of the Church of the Future - Cornelio, Jayeel (Archīum Ateneo, 2018)
This article presents the global challenges that matter to the Church of the future. The First part traces the different facets of the Church as a global phenomenon. It complicates the prevailing view that Christianity is moving to the global south. The second part focuses on two challenges: generational shifts and global inequality. While not exhaustive, the discussion will provide some nuances regarding the issues at stake at a global level. The character of the Church of the future rests on how it responds to these present-day issues that will linger in the years ahead.